Sosial Movement Berbasis Religiusitas: Studi Kasus Gerakan Aksi Bela Islam 212 - Apriani, Adelia Putri; Musyanova, Salma Asmarani; Zaneta, Sherly (Indonesian Democracy Research Center, 2024)
The Islamic Defense Movement 212 is one of the implementations of identity politics in Indonesia. The 212 movement began as a reaction to a statement made by then Jakarta Governor Basuki Tjahaja Purnama (Ahok), in which he urged people to refuse to be influenced by verse 51 in Surah Al-Maidah. This caused turmoil among Muslims in Indonesia, because Ahok was considered blasphemy by Muslims. The existence of the Muslim social movement shows that the 212 Movement is a manifestation of the struggle to defend the religious aspects of Islam that were destroyed by a Jakarta governor in 2016. The purpose of the following journal article is to analyze the extent to which the 212 Islamic defense action movement as a social movement affects the dynamics of community participation. The research method used is a qualitative research approach with a descriptive analysis method, while the data collection procedure for journal articles is through document and literature studies. The results obtained from this research are that this movement succeeded in mobilizing community participation through effective mobilization through religious rhetoric. Solidarity among movement participants emerged because of a moral call to defend religious teachings that were considered threatened. Awareness of religious issues is also one of the positive impacts of participation in the 212 Movement, creating a society that is more aware of religious values and related issues.